Locomotion changes in methamphetamine and amphetamine withdrawal: a systematic review - Kumar, Jaya; Mohamed, Isa Naina; Mohamed, Rashidi; Ugusman, Azizah; Muzaimi, Mustapha; Mohamed, Wael Mohamed Yousef; Yahaya, Mohamad Fairuz; Lin Teoh, Seong; Kamaluddin, Mohammad Rahim; Abdul Hamid, Hafizah; Mehat, Muhammad Zulfadli; Shanmugam, Prem Kumar (Frontiers Media SA, 2024)
Despite extensive preclinical research over the years, a significant gap remains in our understanding of the specific effects of methamphetamine (METH) and amphetamine (AMPH) withdrawal. Understanding these differences could be pivotal to unveiling the unique pathophysiology underlying each stimulant. This may facilitate the development of targeted and effective treatment strategies tailored to the specific characteristics of each substance. Following PRISMA guidelines, this systematic review was conducted to examine alterations in spontaneous locomotor activity, specifically horizontal activity, in animals experiencing withdrawal from extended and repeated administration of AMPH or METH. Original articles were retrieved from four electronic databases, supplemented by a review of the references cited in the published papers. A total of thirty-one full-length articles (n = 31) were incorporated in the analysis. The results indicated that six studies documented a significant increase in horizontal activity among animals, seven studies reported decreased locomotion, and eighteen studies (8 AMPH; 10 METH) reported no significant alterations in the animals’ locomotor activity. Studies reporting heightened locomotion mainly employed mice undergoing withdrawal from METH, studies reporting diminished locomotion predominantly involved rats undergoing withdrawal from AMPH, and studies reporting no significant changes in horizontal activity employed both rats and mice (12 rats; 6 mice). Drug characteristics, routes of administration, animal models, dosage regimens, duration, and assessment timing seem to influence the observed outcomes. Despite more than 50% of papers enlisted in this review indicate no significant changes in the locomotion during the stimulant withdrawal, the unique reactions of animals to withdrawal from METH and AMPH reported by some underscore the need for a more nuanced understanding of stimulant withdrawal.